Pilbarana, a new subterranean amphipod genus (Hadzioidea: Eriopisidae) of environmental assessment importance from the Pilbara, Western Australia - Stringer, Danielle N.; King, Rachael A.; Austin, Andrew D.; Guzik, Michelle T. (Zootaxa, 2022)
The Pilbara and nearby regions in north-western Western Australia have an exceptionally high diversity of short-range endemic invertebrates inhabiting threatened groundwater-dependent habitats. Amphipod crustaceans, in particular, are dominant in these communities, but are poorly understood taxonomically, with many undescribed species. Recent molecular phylogenetic analyses of Pilbara eriopisid amphipods have, nonetheless, uncovered a previously unknown biodiversity. In this study, we formally establish a new genus, Pilbarana Stringer & King gen. nov., and describe two new species, P. grandis Stringer & King sp. nov. from Cane River Conservation Park and P. lowryi Stringer & King sp. nov. from the Fortescue River Basin near the Hamersley Range, using a combination of molecular and morphological data. The new genus is similar morphologically to the two additional Western Australian eriopisid genera, Nedsia Barnard & Williams, 1995 and Norcapensis Bradbury & Williams, 1997, but represents a genetically divergent, reciprocally monophyletic lineage, which can be differentiated by its vermiform body shape, the presence of an antennal sinus, and by the length and form of the antennae and uropods. This research signifies an important contribution to knowledge of Pilbara subterranean communities and has critical implications for future environmental impact assessments and conservation management.